LITERATURE REVIEW: STEAM-BASED E-LKPD FOR ENHANCING STUDENTS’ CRITICAL THINKING SKILLS - Perastiati, Yuli; Andayani, Sutrisni; Rahmawati, Dwi (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
Students’ low critical thinking ability remains a major challenge in school learning and is often driven by the dominance of conventional, teacher-centered instruction, which provides limited opportunities for learners to practice analyzing problems, constructing logical reasoning, drawing conclusions, and reviewing their answers. This situation highlights the need for innovative digital learning materials that promote active, contextual learning aligned with 21st-century skills. This study aims to analyze the impact of STEAM-based E-LKPD on improving students’ critical thinking skills. The study employed a literature review method by analyzing 10 articles retrieved from the Scopus and Google Scholar databases. The synthesis indicates that STEM/STEAM-based E-LKPD is consistently considered feasible and effective in enhancing critical thinking, as reflected in moderate-to-high gains and/or clear performance differences between experimental and control groups. The strongest effects occur when E-LKPD is integrated with problem- or project-based activities and supported by media such as animated videos or interactive applications (e.g., Canva) that facilitate concept visualization, document learning processes, and strengthen students’ reasoning in designing solutions and evaluating findings